The use of narrow band ultraviolet light B in the prevention and treatment of postherpetic neuralgia (A pilot study) - Eman El-Nabarawy (Indian Journal of Dermatology, 2011)
Background: Postherpetic neuralgia (PHN) is a common complication of herpes zoster that is frequently unresponsive to most of the available treatment modalities. Broad band ultraviolet B radiation (UVB) has a well-known anti-inflammatory effect. Moreover, it decreases neural damage and cutaneous nerve density. It was found that broad band UVB might have a role in the prevention and treatment of PHN. Aim: This study was carried out to evaluate the effect of narrow band UVB (nbUVB) in the treatment PHN. Patients and Methods: The study included 17 patients with distressing post herpetic neuralgia. Patients were evaluated using the Verbal Rating Scale (VRS). The patients received nbUVB sessions, three times a week, for a total of 15 sessions or until the pain disappeared. Patients were followed up for a period of 3 months after the end of therapy. Results: Using intention to treat analysis, more than 50% improvement was achieved in 6 (35.29%) and 8 (47.06%) patients, at the end of therapy and after 3 months follow up, respectively. An improvement less that 50% was achieved in 11 (64.71%) and 9 (52.94%) patients, at the end of therapy and after 3 months follow up, respectively. The pain severity assessed by the VRS significantly improved both at the end of sessions (P = 0.005) and after 3 months follow up (P = 0.005). Conclusion: nbUVB may be of beneficial use in the treatment of PHN. Limitation: Small number of patients and limited follow-up period.